The Role of Islamic Financial Literacy, Religiosity, and Trust in Sharia Compliance in Fostering Islamic Bank Reputation and Adoption of Sharia-Compliant Services - Muaidy Yasin; Lalu Edy Herman Mulyono; Mohammad Najib Roodhi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study investigates the impact of Islamic Financial Literacy, Religiosity, Islamic Bank Reputation, and Trust in Sharia Compliance on the Adoption of Islamic Banking Products in West Nusa Tenggara, Indonesia. A cross-sectional survey of 300 respondents was conducted using a structured questionnaire, with data analyzed through Structural Equation Modeling (SEM) using Smart PLS software. The findings reveal that Islamic Financial Literacy and Religiosity significantly influence the Adoption of Islamic Banking Products, both directly and indirectly, via Islamic Bank Reputation. Trust in Sharia Compliance moderates the relationship between Islamic Bank Reputation and Adoption, amplifying its effect. The measurement items were validated through a pilot test, ensuring their reliability and validity. This study offers theoretical and practical insights for Islamic banking institutions, emphasizing the importance of financial literacy, religiosity, and trust in fostering customer adoption of Islamic banking products.